PENGARUH PENGETAHUAN KONSUMEN MUSLIM TENTANG MASLAHAH DAN KHIYAR TERHADAP KEPUTUSAN PEMBELIAN DALAM ISLAM - Rahayu, Jofanda Putri; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2021)
The development of e-commerce in Indonesia like as Tokopedia for buying and selling activities to be easy. However, some seller not promising to apply honesty and benefit in buying and selling activities. So, a consumer caution needed for decide to buy to reduce all the risks. The purpose of this research to analyze the influence of Muslim consumer literacy about maslahah and khiyar on purchasing decisions in Islam. The method used in this research is descriptive quantitative with analysis technique using multiple linear regression . The result of this research explain of maslahah and khiyar have an influence on purchasing decisions in Islam. The consumers lireracy on Tokopedia application users have implemented of maslahah and khiyar according to religious teachings.